Straw production and agronomic performance of soybean intercropped with forage species in no-tillage system - Andrade, Carlos Augusto Oliveira de; Borghi, Emerson; Bortolon, Leandro; Bortolon, Elisandra Solange Oliveira; Camargo, Francelino Peteno de; Avanzi, Junior Cesar; Simon, Jones; Silva, Rubens Ribeiro da; Fidelis, Rodrigo Ribeiro (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the straw production and the agronomic performance of soybean intercropped with oversown forage species, in no-tillage system. A randomized complete block design was carried out with four replicates, in a 5×2+2 factorial arrangement, as follows: five forage species – Urochloa brizantha 'Marandu', Urochloa ruziziensis, Panicum maximum 'Mombaça', Panicum maximum 'Massai', and Pennisetum americanum –, intercropped with soybean over two crop years (2013/2014 and 2014/2015), plus two controls, with P. americanum sowed in succession to soybean or with soybean monocropping followed by winter fallow (traditional cultivation). Soybean yield components and forage straw yield were evaluated. None of the intercropping systems reduced soybean grain yield, compared with monocropped soybean. The oversown species can significantly improve soybean productivity, as is the case for soybean intercropped with P. maximum 'Mombaça', compared with soybean monocropping, followed or not by millet. Panicum maximum 'Mombaça' is the most effective forage species for dry matter accumulation in the fall/spring period.